Nitrenes and nitrenium ions - Falvey, Daniel E., 1961-; Gudmundsdottir, Anna D., 1962- (Hoboken, N.J. : Wiley, 2013)
"Nitrenes and Nitrenium ions are reactive intermediates with monovalent nitrogen atoms. These intermediates have diverse reactivity and physical properties, depending on their structure and spin state. The leading experts in nitrene chemistry have contributed to this book to highlight how spectroscopy and calculations have been used to characterize various nitrene intermediates. Emphasizes have also been placed on identifying the diverse methods to form these intermediates. Furthermore, the reactivity of nitrenes and nitrenium ions is discussed in details and how the reactivity can be used in various applications"--
Machine generated contents note: Preface Contributors Introduction Chapter 1. Ultrafast Studies of Azides and Nitrenes Jin Wang, Matthew S. Platz, The Ohio State University, Ohio, Gotard Burdzinski, Adam Mickiewicz University Poland Chapter 2. Computational Studies of Nitrenes and their Excited State Precursors Subham Vyas, Arthur H. Winter, Christopher M. Haddad, The Ohio State University, Ohio Chapter 3. Nitrenium Ions in Photoaffinity Labeling R. Marshall Wilson, Valentyna Voskresenska Bowling Green State University, Ohio Chapter 4. Nitrenium Ions in Aquoeous Solution Mike Novak, Yue-Ting Wang Miami University, Ohio Chapter 5 Triplet Alkylnitrenes Sivaramakrishnan Muthukrishnan, Ranaweera A. A. U. Ranaweera, Anna D. Gudmundsdottir, University of Cincinnati, Ohio Chapter 6. Electronic Structures of Nitrenium Ions Dan Falvey, University of Maryland, Maryland Chapter 7. Raman Studies of Nitrenium Ions David Lee Phillips, University of Hong Kong, Hong Kong Chapter 8. Matrix Studies of Heterocyclic Nitrenes Curt Wentrup University of Queensland, Australia Chapter 9. Dehydroaromatic Nitrenes Dirk Grote Wolfram Sander, Ruhr-Universitat Bochum, Germany Chapter 10. Synthetic Applications of Nitrenium Ions Duncan Wardrop, University of Illinois-Chicago, Illinois Chapter 11. Flourinated Nitrene Precursors Elisa Leyva, Denisse de Loera Socorro Leyva Jimenez-Catano, Univ. Autonoma San Luis Potosi, San Luis Potosi, Mexico Chapter 12. Acylnitrenes Nina Gritsan, Institute of Chemical Kinetics and Combustion Novosibirsk, Russia Index.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Nitrenes; Nitrogen compounds; Electronic books